Strategies of vocabulary learning employed by low-frequency-word level students in international class - Vinindita Citrayasa; Elisabeth Marsella; Maria Setyaningsih Nernere (Journal on English as a Foreign Language, 2022)
The application and development of vocabulary learning strategies (VLS) lead to acquiring a more extensive vocabulary size and better performance in language acquisition. Students with different proficiencies might employ various VLS in their language learning process. This study aims to describe and analyze the vocabulary learning strategy used by low-frequency-word level students identified by vocabulary size test they took previously. This study adopted mix-method research by using questionnaires and interviews. The participants were university students of international programs majoring in industrial engineering, civil engineering, and business and economics. The students were identified in low-frequency-word level who were considered able to understand wide reading and specialized study. The findings showed that low-frequency-word level students primarily used dictionary, guessing, and activation strategies. The social strategy was identified as another alternative strategy to learn vocabulary. Google Translate was the most popular translating tool due to its practicality. Guessing meaning strategy was done when failing to find the desired words using an online translation machine. Moreover, the students used social media as the platform to implement the activation strategy. Meanwhile, note-taking, rehearsal, metacognitive strategies belong to the least used VLS as the students are not into intentional vocabulary learning.